Comparative trends of accidental to intentional mortalities over a one-year period at a tertiary care centre - Sharma, Dharmendra K.; Meena, Prathvi R.; Punia, Rakesh K.; Pathak, Deepali (International Journal of Research in Medical Sciences, 2018)
Background: The trends of deaths due to unnatural incidents are on the rise each year throughout the world, including India. Incremental trends have been observed in all mortalities throughout the country. Although all these mortalities seem preventable, yet not much has been achieved over the years. Intentional mortalities are yet more preventable as compared to non intentional ones. The trends of unnatural deaths were observed at a tertiary care centre of the capital city of Rajasthan to determine the comparative magnitude of such fatalities to predict possible reasons for them. Methods: An observational study was carried out for a one year period (2013-14) at the Department of Forensic Medicine of an apex institution of the capital metropolitan city to determine the comparative trends of accidental to suicidal and homicidal deaths amongst the medico-legal autopsies carried out over the study period. The results were analysed to look into the probable reasons for these preventable deaths. Results: Accidental fatalities contributed maximally followed by suicides and homicides. All types of unnatural deaths were more commonly observed in young adult male population. Road accidents were the major offenders followed by thermal injuries and falls. Intentional fatalities due to self harm or other human beings shared a considerable burden among unexpected mortalities over the study region. Conclusions: Majority of the reported fatalities were preventable deaths occurring amongst the active and productive population and hence, it is of utmost importance to analyse such deaths to suggest remedial measures bring down the toll of such causalities.